Retrospective comparison of parent‐reported genetics knowledge, empowerment, and familial uptake of cardiac screening between parents who received genetic counseling by a certified genetic counselor and those who did not: A single US academic medical center study. Issue 4 (8th March 2022) - Hancock, Bailey; Miller, Erin M.; Parrott, Ashley; Weaver, Kathryn Nicole; Tretter, Justin T.; Pilipenko, Valentina; Shikany, Amy R.
Abstract: Bicuspid aortic valve (BAV) is the most common congenital heart defect, which can cause severe cardiac complications. BAVs cluster in families and demonstrate high heritability. Cardiac screening for first‐degree relatives of individuals with a BAV is recommended. This retrospective two‐group study evaluated the impact of cardiovascular genetic counseling provided by a board‐certified genetic counselor on parent‐reported outcomes by comparing parental responses of those who received genetic counseling by a genetic counselor (GC group) for family history of BAV to those who did not (non‐GC group). A retrospective chart review from May 2016 to June 2019 identified 133 pediatric patients with an isolated BAV. Parents of eligible probands were invited to complete an online survey assessing genetics knowledge, empowerment (Genomics Outcome Scale), and familial uptake of cardiac screening. Surveys were completed by 38/97 (39%) parents in the non‐GC group and 20/36 (56%) parents in the GC group. The median genetics knowledge score was not significantly different between the two groups (GC group: 8, range 3–11 out of a maximum possible of 12; non‐GC group: 7, range 2–11; p  = .08). The mean empowerment score was not significantly different between the two groups (GC group: mean 24.6, SD 2.2; non‐GC group: mean 23.2, SD 3.5; p  = .06). The uptake of cardiac screening was significantly higher in the GC group with 39/59 (66%) total first‐degree relatives reported as having been screened compared with 36/91 (40%) in the non‐GC group ( p  = .002). Parent‐reported outcomes in our study suggest that receiving genetic counseling by a board‐certified genetic counselor significantly increased familial uptake of cardiac screening for first‐degree relatives of pediatric patients with a BAV. Studies with larger sample sizes are needed to confirm the findings of this study; however, a referral to a genetic counselor should be considered for patients with a BAV. Abstract :